(untitled) (International Journal of Engineering and Computer Science, 2014)
Optical wireless communications offer a viable alternative to radio frequency communication for rural and urban where high performance links are needed. This paper presents a review of the most significant issues related to optical communication technology, which will enable the realization of future high performance and cost-effective optical wireless systems. Several possible configurations for optical wireless systems, modulation, and multi-access techniques are presented as well as their advantages and limitations discussed